2010
DOI: 10.1111/j.1471-0528.2010.02800.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of active management and expectant management of the third stage of labour: a Swedish randomised controlled trial

Abstract: Objective To compare blood loss in women actively and expectantly managed in the third stage of labour. Design Randomised controlled trial (RCT).Setting Two delivery units at a Swedish university hospital.Population Healthy women with normal pregnancies, at gestational age 34-43 weeks, with singleton cephalic presentation and expected vaginal delivery.Methods The women were randomly allocated to either active (n = 903) or expectant (n = 899) management of the third stage of labour.Main outcome measures The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 35 publications
1
46
1
2
Order By: Relevance
“…The incidence of PPH was considerably higher in the study group with VWD compared to the general incidence in high resource countries [11, 12, 16, 37]. The incidence of primary PPH was 44% in our study group, thus higher than what has been described in the previous studies where similar methods of data collection were used, and similar to the reported incidence in studies investigating PPH by patient recall [2, 18, 20, 2224, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of PPH was considerably higher in the study group with VWD compared to the general incidence in high resource countries [11, 12, 16, 37]. The incidence of primary PPH was 44% in our study group, thus higher than what has been described in the previous studies where similar methods of data collection were used, and similar to the reported incidence in studies investigating PPH by patient recall [2, 18, 20, 2224, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary PPH is defined as any abnormal bleeding 24 hours to six weeks postpartum, regardless of volume. In high-resource countries where uterotonic drugs are used routinely, the reported incidence of primary PPH, severe primary PPH and secondary PPH is respectively 5–19%[1214], 4–10% [13, 15, 16] and 1–3% [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on a review of approximatley 15,000 births, the duration of vaginal birth used in this study was assumed to be 65 minutes (Janakiraman et al, 2010); placental delivery was assumed to be 15 minutes (Jangsten et al, 2011). We assumed a ratio of women having their first birth to women who have previously given birth of 40/60 based on Magee’s delivery patterns.…”
Section: Methodsmentioning
confidence: 99%
“…Active management of the third stage of labor reduces the risk of postpartum uterine atony, and includes prophylactic oxytocin administration with delivery, vigorous fundal massage lasting at least 15 seconds, and controlled cord traction to deliver the placenta. 55 Oxytocin is the preferred first-line uterotonic for both prophylaxis and treatment of postpartum hemorrhage, because it is clearly shown to decrease blood loss during the third stage of labor and decreases need for additional uterotonics, 55,56 even after prolonged oxytocin infusions for the induction or augmentation of labor. Rapid intravenous infusion of oxytocin may cause peripheral vasodilation, hypotension, flushing, nausea, chest pain, myocardial ischemia, and, in the face of substantial hemorrhage, cardiovascular collapse.…”
Section: Stagementioning
confidence: 99%